2016
DOI: 10.21767/2386-5180.100083
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Cortisol Increases after One Immersive Simulation but the Repetition of Sessions does not Blunt it

Abstract: Objective: Simulated life-threatening medical emergencies generate stress that can be apprehended by measurement of salivary cortisol (SC). The aim of this study was to analyze SC level in multidisciplinary teams (MDTs) members during immersive simulation and to study its evolution over time with repetition of simulation sessions in all team members.Methods: 48 participants constituted 12 Emergency Medical Service MDTs made up of 4 members each. Six MDTs underwent 9 simulations (experimental group) and 6 under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…We also found that HR and HRV in the frequency domain (LF/HF ratio) increased during all repeated sessions in both groups. In another study pertaining to the same randomized control trial, results suggested that salivary cortisol similarly increased during all repeated simulations and decreased during debriefing in both experimental and control groups [19]. On this subject, the Yerkes-Dodson law on tendency for optimal performance models the relationship between performance and stress as an inverted-U curve: stress improves performance up to a peak, and subsequently drives it down [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that HR and HRV in the frequency domain (LF/HF ratio) increased during all repeated sessions in both groups. In another study pertaining to the same randomized control trial, results suggested that salivary cortisol similarly increased during all repeated simulations and decreased during debriefing in both experimental and control groups [19]. On this subject, the Yerkes-Dodson law on tendency for optimal performance models the relationship between performance and stress as an inverted-U curve: stress improves performance up to a peak, and subsequently drives it down [36].…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that stress increased during simulation and decreased during and after debriefing [14,18]. Repeated simulations using salivary cortisol did not blunt it during the simulation phase [19]. However, to our knowledge, up until now no study has analyzed level of stress in participants during the whole day of planned simulation training and its evolution when simulations are repeated.…”
Section: Introductionmentioning
confidence: 99%